Analysis of the Susceptibility and Seriousness of Hypertension Control Measures with Compliance with Routine Health Checks (Blood Pressure Checks) - Aris, Muhammad; Risky, Sartini; Rahmawati, Rahmawati (Magister Kesehatan Universitas Mandala Waluya, 2026)
Introduction: Hypertension is a serious medical condition that can lead to various health complications and can be significantly prevented through regular blood pressure monitoring. The monthly trend of hypertension in the five districts with the highest number of hypertension cases in Kolaka Regency prompted researchers to conduct a study on the analysis of the relationship between susceptibility and seriousness of hypertension control measures and compliance with routine health checks (blood pressure checks). Method: The type of research used is quantitative research with an analytical observation method and a Partial Least Squares (PLS) research design. The population was 570 people and the sample was 235 people using Sampling (area sampling) in the sampling. Result: The vulnerability is 0.326 (positive direction), the T statistic is 3.655, and the p-value is 0.000. The severity is -0.672 (negative direction), the T statistic is 5.189, and the p-value is 0.000. The test results show that the p-value is <0.05. Conclusion: Vulnerability and seriousness are related to hypertension control measures with compliance with routine health checks (blood pressure checks).